ANALYSIS OF MICRO INSURANCE MODELS FOR FISHERMANS (STUDY IN SUKABUMI AND PANGANDARAN PORT) - Rimawati Rimawati; Tuti Kurnia; Anas Alhifni (Jurnal Ekonomi dan Bisnis Islam | Journal of Islamic Economics and Business, 2019)
This study aims to determine the response of fishermen to insurance, so it can be seen how the right insurance model for fishermen in order to support the accessibility of capital to financial institutions such as LKMS. The determination of the insurance model in this study uses the Analytic Network Process (ANP) method, where the decision is made by considering and validating empirical experience. The results of this study indicate that the most appropriate insurance model is Partner Agent with a value of 0.4774. Partners who are invited to work together in this regard are KUD Fishermen. The most appropriate insurance product is a Health Insurance product with a weight of 0.4878. Based on these results the researchers made several alternative microinsurance models in accordance with each category of fishermen including, the KUDN Partner Model for Small Fishermen, the Micro-ABK Model for Workers Fishermen, and the Full Service Insurance Company (LPPA) Model for Fishermen employer.